Analysis of the Procurement of Civil Servants in Deli Serdang Regency (Study at the Regency Regional Personnel Agency Deli Serdang) - Wahyu Ramadhan; Rudi Salam Sinaga; Adam Adam (Budapest International Research and Critics University, 2021)
This study aims to determine the Procurement of Civil Servants in Deli Serdang Regency. This study used qualitative approach. The result of the study Procurement of civil servants at the Regional Pegadaian Agency of Deli Serdang Regency is carried out through the stages: planning, determining requirements, announcements, applications, which are then followed by screening and appointment to civil servant candidates, followed by appointment to civil servants.The constraint factors faced in the implementation of the procurement of civil servants are: the lack of a number of qualified applicants so that there is a compulsion to accept applicants whose test scores are less than standard, supervision of the procurement process is difficult because there are so many parties with an interest in the procurement process even high-ranking government officials. Also take advantage of the procurement process for their personal interests, as well as efforts by civil servant applicants to approach government officials by giving bribes to graduate as civil servants.